The 10th Grade Students' Folding Back Process in Solving Decimal Problem with Field-dependent and Field-independent Cognitive Styles - Nuswantoro, Ari Wahyudi; Siswono, Tatag Yuli Eko; Khabibah, Siti (Journal of Mathematical Pedagogy (JoMP), 2020)
The purpose of this study was to describe the folding back process of 10th grade students with field-dependent (FD) and field-independent (FI) cognitive styles in solving decimal problems. This research was conducted explorative with a qualitative descriptive approach. The subjects in this study were two students grade X at SMA Al Muslim Surabaya. The subjects chosen based on a different of the FI-FD cognitive style was carried out by giving a cognitive style test, then a group of students with a cognitive style of FI and a group of students with a cognitive style of FD were selected. This results is the GFI subject can determine the definition of a decimal number when presenting a decimal number on a ruler and at that time the GFI subject experiences folding back. Folding back also occurs when the GFI subject determines the size ratio of decimals, decimal number operations and when converting decimal numbers into fractions and percentages. Then for GFD subjects must be given a stimulus first using the original numbers given commas and zeros, then the GFD subject changes his opinion on decimal numbers.Keywords: Folding back, decimal problem, field-dependent (FD), field-independent (FI), cognitive styles